Epithelial Alteration Associated With Recovery From Laryngeal Squamous Metaplasia in Rats: Kinetics of Recovery From a Test Item-Related Change. (February 2021) - Macri, Nicholas P.; Keenan, Charlotte M.; Hoffman, Gary M.; Cracknell, Stuart; Schofield, Mike; Bond, Andrew
Squamous metaplasia is a nonspecific adaptive response to chronic irritation in the larynx and is often diagnosed as a test item-related change in rat inhalation studies. Investigating scientists are frequently asked to assess the adversity of laryngeal squamous metaplasia and to interpret its relevance to human risk. One factor in predicting relevance to human risk is the kinetics (degree and speed) of recovery following the cessation of exposure to the test item. Most reports describing recovery from squamous metaplasia in the rat larynx discuss the more severe end of the spectrum of metaplastic change (moderate to severe) and include relatively long (6 weeks or more) recovery periods. We conducted 2 studies to evaluate the toxicity and recovery from any potential effects of 4-(Chloro-2-methylphenoxy) butyric (MCPB) acid, a herbicide, when administered by inhalation to young male Sprague Dawley rats for 3 to 4 weeks. The studies resulted in minimal to moderate laryngeal squamous metaplasia for which we describe the kinetics of recovery over 1 to 4 weeks. We found that the microscopic change epithelial alteration, which is normally considered to be a precursor in the development of squamous metaplasia, can occur as a transitional stage between squamous and normal epithelium during recovery.